1986
DOI: 10.1149/1.2108680
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Morphology of GaAs Etching in Aqueous CrO3 ‐  HF  Solutions

Abstract: The etching of n‐ and p‐type normalGaAs in aqueous CrO3‐HF solutions, both under illumination and in the dark, has been studied. On the basis of two ternary composition diagrams, three regions of different etching kinetics can be delineated. These are also regions of different surface morphology after etching. For low false[HFfalse]/false[CrO3false] ratios and false[HFfalse]<10M the etching process is kinetically controlled. The etch rate depends on false[HFfalse] and is independent of false[CrO3fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…From an extensive study of GaAs etching in CrO3-HF solutions reported elsewhere (10), it was clear that the ratio of the HF and CrQ concentrations is very important for the etching kinetics. Consequently, the etching and electrochemical results, described in this section, are classified on the basis of this ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an extensive study of GaAs etching in CrO3-HF solutions reported elsewhere (10), it was clear that the ratio of the HF and CrQ concentrations is very important for the etching kinetics. Consequently, the etching and electrochemical results, described in this section, are classified on the basis of this ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In the second part of this paper, a model is proposed which can explain both the etching and electrochemical results. The morphological aspects of etching in CrO~-HF solutions will be discussed in a separate paper (10).…”
mentioning
confidence: 99%
“…The total morphology of the etch features depends, however, upon both the crystallographic and chemical nature of the defect, often assuming a complex shape. 4,5 The mechanism of electroless etching, studied in detail in GaAs and InP, 3,6,7 involves multistep reactions taking place simultaneously at the semiconductor surface. These reactions are: reduction of oxidizing agent followed by injection of holes into the solid, oxidation of the solid using holes, and dissolution of the products.…”
Section: Introductionmentioning
confidence: 99%
“…11) We measured the etch pit density (EPD) using a solution of CrO 3 -HF-H 2 O with ½HF=½CrO 3 ¼ 3 and ½HF ¼ 5M (M: mole/l). 18) The EPD was 4 Â 10 5 cm À2 , which is less than the TD density determined using p-TEM. The EPD underestimated the true TD density.…”
Section: Resultsmentioning
confidence: 71%